TEMUAN MENARIK HASIL EKSPLORASI ETNOMATEMATIKA PADA BATIK GAJAH OLING BERDASARKAN KONSEP GEOMETRIS - Karimah Salasari; Titik Sugiarti; Erfan Yudianto; Toto' Bara Setiawan; Dinawati Trapsilasiwi (FKIP Universitas Jember, 2019)
Ethnomatematics as link between culture and mathematics is a multicultural mathematical activity that uses culture in making connections with mathematics topics so as to motivate students to preserve their own culture while learning mathematics. The purpose of this reasearch are to explore ethnomathematics in Gajah Oling’s batik based on geometric concepts. The type of reaserch is qualitative with an ethnographic approach. Data collection methods used are observation and interviews. The subject of this reasearch is a design maker Gajah Oling’s batik. This research focuses on intersesting discovery from the exploration results, that is making pattern of Gajah Oling’s batik shirt. In the process of making pattern of Gajah Oling’s shirt, ethnomathematics seen on design and measuring activities. In desiging activities geometric concepts such as translation and reflection emerge, while in measuring activities, design makers use mathematics to determine the design size so that the fabric meeded to make a shirt can be minimized as little as possible.Keywords: Ethnomatematics, cocoa farmers, culture.